2010
DOI: 10.1016/j.exppara.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachta indica A. Juss (neem) induced morphological changes on oocytes of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) tick females

Abstract: Many studies have been conducted with plants whose extracts have the potential to be used for pest control. One of these plants is Azadirachta indica (neem), whose main active ingredient is azadirachtin, a compound shown to have acaricide and insecticide activity. Rhipicephalus sanguineus (brown dog tick) is currently considered to be an "urban pest," because of its high levels of infestation and its ability to attack humans. In the present study partially and fully engorged R. sanguineus females were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 17 publications
10
40
1
Order By: Relevance
“…Moreover, the presence of vacuoles full of electron-dense bodies in the interdigitations indicated the possible establishment of a defense mechanism for removing damaged or toxic materials (e.g., organelles, membrane residues, and the chemical compound itself) that should not remain or reach the interior of the oocyte. Our results corroborate those obtained in studies conducted by Denardi et al (2010) when he treated female R. sanguineus ticks with the aqueous extract of ''Neem'' leaves.…”
Section: Microscopy Research and Techniquesupporting
confidence: 95%
See 1 more Smart Citation
“…Moreover, the presence of vacuoles full of electron-dense bodies in the interdigitations indicated the possible establishment of a defense mechanism for removing damaged or toxic materials (e.g., organelles, membrane residues, and the chemical compound itself) that should not remain or reach the interior of the oocyte. Our results corroborate those obtained in studies conducted by Denardi et al (2010) when he treated female R. sanguineus ticks with the aqueous extract of ''Neem'' leaves.…”
Section: Microscopy Research and Techniquesupporting
confidence: 95%
“…Juss.) (Denardi et al, 2010), as well as extracts from other plants of the Asteraceae family (Ribeiro et al, 2008). More recent studies have shown that derivatives of castor oil (Ricinus communis), especially an ricinoleic acid ester of this oil, when incorporated into animal feed, can drastically interfere in the physiology of the salivary glands and ovaries of R. sanguineus ticks that feed on these animals, offering an effective contribution to the reduction of tick populations in the environment (Arnosti et al, 2011a,b).…”
Section: Introductionmentioning
confidence: 97%
“…In ticks, the use of neem products showed relevant effects for the control of Amblyomma variegatum (Ndumu et al 1999), Hyalomma dromedarii (Al-Rajhy et al 2003), Hyalomma anatolicum excavatum (Abdel-Shafy and Zayed, 2002), Rhipicephalus decoloratus (Choudhury 2009), Rhipicephalus (Boophilus) microplus (Srivastava et al 2008;Broglio-Micheletti et al 2010) and R. sanguineus (Denardi et al 2010(Denardi et al , 2011(Denardi et al , 2012, affecting reproductive processes or even causing mortality.…”
Section: Introductionmentioning
confidence: 96%
“…It is also a known disruptor of larval development of insects (Schmutterer 1990;Singh 2003;Rharrabe et al 2008). However, the reports are scarce about the efficacy of it on oogenesis (Sayah et al 1996;Denardi et al 2010) and reproductive potential of parasites. Moreover, no such information is available on the crustacean reproductive biology.…”
Section: Introductionmentioning
confidence: 98%